Stepper motor controller using PIC / Norsufia Arianti Md. Norani and Noor Zawani Ramli - Md. Norani, Norsufia Arianti; Ramli, Noor Zawani (2005)
A stepper motor is a type of electric motor that is used when something has to be positioned very precisely or rotated by an exact angle. Because of this characteristics, stepper motor is fully used in the industries which need the equenced steps of movements. Some application of this stepper motor can be look at conveyer in industries, lifts, parabola antenna and many mores. In this project, we would like to show stepper motor controller functioned using PIC 16F84A which is the heart of this project. We programmed the input output in the IC to make it perform some action on the stepper motor controller. The proposed of this project is to provide more reliable stepper motor controller by using programming software.